Report on research findings: Improving access to social and economic services for people with disability in Lao PDR - Fielding, Angela; Thoresen, Stian; Gillieatt, Sue; Nguyen, Liem; Blundell, Barbara (2016)
This workshop will present the findings from the Australian Aid funded research “Improving Access to Social and Economic Services for People with Disability in Lao PDR (2013-16)”. The research has been conducted by a team from Curtin University School of Occupational Therapy and Social Work, with our Implementing Partner LDPA, through a Memorandum of Understanding with the Ministry of Labour and Social Welfare.